STRUKTUR VEGETASI MANGROVE DI PESISIR PANTAI DESA DAMBALO KECAMATAN TOMILITO KABUPATEN GORONTALO UTARA - Alexander Ruruh; Ernikawati Ernikawati (Jurnal Penelitian Kehutanan BONITA, 2021)
Mangroves are tropical coastal vegetation communities dominated by several unique tree species that can be affected by tides. Damage to mangrove forests can be caused by two main factors, namely human activity factors and natural factors. The purpose of this study was to analyze the structure of mangrove vegetation by looking at density, frequency, Impact Value Index (IVI) and species diversity (H ') on the coast of Dambalo Village, Tomilito Sub-district, North Gorontalo District. The method used is a combination of the path method and the checkered line method so that measuring squares are created within the paths. The results showed that the number of mangrove diversity was 11 species, with the Importance Value Index at the tree level of the Rhizophora apiculata species having the highest value of 61.28% and the seedling phase with the same species Rhizophora apiculata having the highest index of importance of 29.80%. The main conclusion from this research is that the mangrove vegetation structure has an abundant level of species diversity. This shows that the index of species diversity in mangrove vegetation is H '= 2.2692 that species diversity is abundant.